Evaluación de los riesgos ambientales originados en pozos petroleros: con énfasis en aguas subterráneas y superficiales (2018)
The objective of this study is the evaluation of the environmental risks originated in the activities developed in oil wells, with emphasis on the contamination of ground and surface water. In order to achieve this, an exhaustive investigation was carried out that allowed the compilation of studies on cases in the industry that allowed the identification of risks associated with water resources. The risk analysis developed shows that the impact generated by the oil industry on the water bodies is high, which is why within this document the activities that could give rise to a possible affectation of the resource were considered.